A Fe-SSZ-13 molecular sieve composite catalyst and its preparation method and application

By adding boron nitride whiskers and organic-inorganic nanocomposites to the Fe-SSZ-13 molecular sieve, the problems of insufficient catalytic activity and narrow temperature range are solved, and efficient and stable nitrogen oxide removal is achieved, which is suitable for long-term use under industrial conditions.

CN119016113BActive Publication Date: 2025-04-01SHANDONG ZHOULAN ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411138892.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-04-01
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Fe-SSZ-13 molecular sieve has insufficient catalytic activity, a narrow working temperature range, and is susceptible to moisture and sulfides, resulting in a decrease in long-term stability and activity.

Method used

The Fe-SSZ-13 molecular sieve composite catalyst is used to improve the mechanical properties, thermal stability and sulfur resistance of the catalyst by adding boron nitride whiskers, organic-inorganic nanocomposite materials, stearic acid, glycerin and organic binder.

Benefits of technology

It significantly improves the catalytic activity and working temperature range of the catalyst, enhances hydrothermal stability and sulfur resistance, and is suitable for long-term operation under industrial conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119016113B_ABST
    Figure CN119016113B_ABST
Patent Text Reader

Abstract

The invention discloses a Fe-SSZ-13 molecular sieve composite catalyst and its preparation method and application, belonging to the technical field of denitration catalysts. The Fe-SSZ-13 molecular sieve composite catalyst of the present invention includes the following raw materials by weight: 60 to 80 parts of synthetic Fe-SSZ-13 molecular sieve, 5 to 10 parts of boron nitride whiskers, 15 to 20 parts of organic-inorganic nanocomposites, 0.5 to 1 part of stearic acid, 1 to 2 parts of glycerol and 3 to 5 parts of organic binder. The Fe-SSZ-13 molecular sieve composite catalyst prepared by the present invention not only has high catalytic activity and a wide operating temperature range, but also has good hydrothermal stability and sulfur resistance. The addition of boron nitride whiskers significantly improves the mechanical properties and wear resistance of the catalyst, and is suitable for long-term operation under industrial conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of denitration catalysts, and specifically relates to a Fe-SSZ-13 molecular sieve composite catalyst and a preparation method and application thereof. Background Art

[0002] Environmental issues have become a hot topic in society today, among which the harm caused by nitrogen oxides to the environment is becoming increasingly significant. As a typical atmospheric pollutant, there are many types of nitrogen oxides, including NO, NO2, N2O3, etc. With the increasing demand for fossil fuels due to industrial development, the emission of nitrogen oxides is increasing. Strengthening the control of nitrogen oxide pollution is an important issue that needs to be urgently addressed in air pollution control projects. Catalytic denitrification is a method used to reduce nitrogen oxides (NO x ) emission technology, under the action of catalyst, oxidizes nitrogen monoxide into nitrogen dioxide, and the generated NO2 can be further treated by water absorption or other chemical methods to reduce its emission into the atmosphere.

[0003] Molecular sieves are widely used as catalyst carriers because of their unique pore structure, high specific surface area and adjustable acidity. Among them, ZSM-5 molecular sieve is an aluminosilicate molecular sieve with MFI topology, which has a regular microporous structure and stable thermodynamic properties. Cu / ZSM-5 is a common catalyst, in which copper ions are exchanged into the pores of ZSM-5 molecular sieve as active centers. Cu / ZSM-5 molecular sieve has good performance in catalytic decomposition of NO at lower temperatures. SSZ-13 molecular sieve belongs to CHA topology and is a small pore size molecular sieve. Cu-SSZ-13 is a particularly effective catalyst and is widely used in NH3-SCR reactions. CHA molecular sieve also has CHA topology and can be prepared into nanosheets, which are suitable for low-temperature denitration reactions and can be loaded with different metal ions, such as copper or iron, to enhance catalytic performance. In addition to the above-mentioned molecular sieves, other types of molecular sieves have also been used in the study of denitration catalysts, such as MCM-22, Beta and Y molecular sieves.

[0004] Iron-based SSZ-13 molecular sieve (Fe-SSZ-13) is a highly efficient catalyst for the removal of nitrogen oxides (NO x ). Although it has many advantages in catalytic performance, it also has some disadvantages, mainly including:

[0005] (1) Fe-SSZ-13 molecular sieve has the problem of insufficient catalytic activity.

[0006] (2) The working range is relatively narrow. When the temperature is too low, the catalytic activity decreases, and when the temperature is too high, the molecular sieve structure is damaged.

[0007] (3) Flue gas often contains moisture. The presence of high temperature and moisture may cause the molecular sieve structure to be destroyed, thereby affecting the long-term stability of the catalyst.

[0008] (4) Industrial waste gas usually contains a certain amount of sulfides, which may interact with iron sites and cause catalyst deactivation. Sulfur poisoning can significantly reduce the activity and selectivity of the catalyst. Summary of the invention

[0009] The purpose of the present invention is to provide a Fe-SSZ-13 molecular sieve composite catalyst and its preparation method and application, so as to solve the problems of insufficient catalytic activity, narrow operating temperature range and susceptibility to moisture and sulfide of the above-mentioned Fe-SSZ-13 molecular sieve. The Fe-SSZ-13 molecular sieve composite catalyst prepared by the present invention not only has high catalytic activity and a wide operating temperature range, but also has good hydrothermal stability and sulfur resistance. The addition of boron nitride whiskers significantly improves the mechanical properties and wear resistance of the catalyst, and is suitable for long-term operation under industrial conditions.

[0010] To achieve the above object, the present invention provides a Fe-SSZ-13 molecular sieve composite catalyst, which comprises the following raw materials in parts by weight:

[0011] Synthetic Fe-SSZ-13 molecular sieve 60~80 parts

[0012] Boron nitride whiskers 5~10 parts

[0013] 15~20 parts of organic-inorganic nanocomposite materials

[0014] 0.5~1 part of stearic acid

[0015] 1~2 parts glycerin

[0016] 3~5 parts of organic binder;

[0017] The preparation method of synthetic Fe-SSZ-13 molecular sieve is:

[0018] The Fe-complex solution is added dropwise to the aluminosilicate molecular sieve gel, and after the addition is completed, amino graphene is added, ultrasonicated and stirred evenly, a hydrothermal reaction is carried out, and the mixture is filtered, washed and dried to obtain a synthetic Fe-SSZ-13 molecular sieve;

[0019] The preparation method of the organic-inorganic nanocomposite material is as follows:

[0020] (1) mixing halloysite nanotubes, copper oxide and titanium silicon carbide to obtain a mixed material;

[0021] (2) adding the mixed material into a ball mill, then adding ethanol and sodium dodecyl sulfate into the ball mill, and then adding a grinding medium for grinding. After the grinding is completed, filtering, washing, and drying to obtain a modified inorganic material;

[0022] (3) dissolving carboxymethyl cellulose in water to form a carboxymethyl cellulose solution, adding ethylene oxide to the carboxymethyl cellulose solution, and after the heating reaction is completed, continuing to add diethyl phosphate, and after the temperature is raised to complete the reaction, filtering, washing, and drying to obtain modified carboxymethyl cellulose;

[0023] (4) Adding the modified inorganic material to ethanol and adding 3-aminopropyltriethoxysilane, reacting at room temperature to obtain a mixed solution 1, adding the modified carboxymethyl cellulose to water to form a mixed solution 2, adding the mixed solution 1 to the mixed solution 2, heating to react, filtering, washing, and drying to obtain an organic-inorganic nanocomposite material.

[0024] Due to the unique pore structure and high specific surface area of ​​molecular sieve, it is widely used as a carrier in denitration catalysts, but the distribution of active ingredients in the molecular sieve will directly affect the overall catalytic activity of the catalyst. In the synthesis process of Fe-SSZ-13 molecular sieve, the present invention not only uses a complexing agent to form a complex with an iron source, but also specifically adds amino graphene, which significantly improves the catalytic activity of the catalyst. Analysis of the reasons: The complexing agent can form a stable complex with iron ions, which helps to distribute iron ions more evenly in the molecular sieve framework, avoid particle agglomeration, and thus improve the utilization rate of iron. The introduction of amino graphene can be used as a carrier or auxiliary agent to promote the stable existence of iron species on the surface of the molecular sieve. In addition, amino graphene has good conductivity and a large specific surface area, which can promote the process of electron transfer, thereby improving the activity of the catalyst. The amino groups on the amino graphene can participate in the catalytic reaction as active sites, especially for the adsorption and activation process of nitrogen oxides.

[0025] The present invention continues to study and find that although the synthetic Fe-SSZ-13 molecular sieve has good catalytic activity at a specific temperature, the operating temperature range is relatively narrow during actual application. When the temperature is too low, the catalytic activity decreases, and when the temperature is too high, the molecular sieve structure is damaged. In order to solve the above problems, the present invention uses the synthetic Fe-SSZ-13 molecular sieve as the main component, and adds boron nitride whiskers, organic-inorganic nanocomposite materials, stearic acid, glycerol and organic binders to mix to prepare a composite catalyst, which further expands the operating temperature range of the composite catalyst. Analysis of the reasons: First, boron nitride whiskers have high thermal stability and good thermal conductivity, can maintain structural stability at high temperatures, and help to improve the thermal stability of the catalyst. High thermal conductivity can help to quickly conduct heat and reduce local overheating, thereby improving the stability of the catalyst at high temperatures. The high strength of boron nitride whiskers can also improve the overall mechanical strength of the catalyst and reduce structural damage at high temperatures. The organic-inorganic nanocomposite material includes inorganic materials and organic materials, which can cooperate with each other to adjust the thermal expansion coefficient of the catalyst and reduce the structural damage caused by thermal expansion and contraction. Stearic acid, as a lubricant, can improve the molding properties of the catalyst and help maintain the integrity of the catalyst shape at high temperatures. Organic binders help improve the molding properties of the catalyst and ensure that the catalyst maintains a good shape and structure at high temperatures.

[0026] The present invention also found that although the catalytic activity of the composite catalyst has been improved and the operating temperature range has been expanded, in the actual application process, there are still adverse effects of moisture and sulfide in the flue gas itself on the catalyst. The present invention continues to design an organic-inorganic nanocomposite material, wherein the inorganic material includes halloysite nanotubes, copper oxide and silicon titanium carbide, and the organic material includes twice-modified carboxymethyl cellulose. The organic-inorganic nanocomposite material significantly improves the water resistance and sulfur resistance of the composite catalyst. Analysis of the reasons: Inorganic components such as halloysite nanotubes, copper oxide and silicon titanium carbide in the organic-inorganic nanocomposite material can provide additional mechanical strength and stability, helping the catalyst to maintain structural integrity in a humid environment. The surface properties of the composite material can be adjusted by modifying the inorganic material (such as using a silane coupling agent such as 3-aminopropyltriethoxysilane), so that it can maintain a certain hydrophilicity to adsorb reactants and have a certain hydrophobicity to resist the influence of moisture on the activity of the catalyst. The organic components (such as carboxymethyl cellulose) in the nanocomposite are combined with the inorganic components to optimize the pore structure and reduce the pore collapse caused by the entry of water molecules, thereby maintaining the high specific surface area and good diffusion performance of the catalyst. Copper oxide, as a metal oxide, can effectively capture and convert sulfur compounds, prevent them from interacting with the active center of the catalyst, and thus protect the Fe-SSZ-13 molecular sieve from sulfur contamination. The inorganic components in the organic-inorganic nanocomposite, especially halloysite nanotubes and silicon titanium carbide, can play a certain barrier role due to their special structure and chemical properties, preventing sulfides from diffusing into the interior of the catalyst and reducing sulfur poisoning. Therefore, there is a synergistic effect between the different components in the organic-inorganic nanocomposite, and the multi-level pore structure formed helps to improve the moisture resistance of the catalyst. At the same time, these pore structures can also serve as sulfur capture sites. The organic-inorganic nanocomposite jointly improves the moisture resistance and sulfur resistance of the composite catalyst.

[0027] Preferably, the Fe-complex solution is prepared by:

[0028] The iron source is added into water and stirred until it is completely dissolved to form an iron solution, and a complexing agent is added dropwise into the ferrous iron solution and stirred sufficiently to obtain an Fe-complex solution;

[0029] The iron source is one of ferric chloride and ferric nitrate; the complexing agent is one of N-aminoethyl-γ-aminopropyltrimethylsilane and disodium ethylenediaminetetraacetate;

[0030] The molar ratio of iron source to complexing agent is 0.3~0.5:0.1~1;

[0031] The amount of amino graphene added is 3-5% of the mass of the iron source;

[0032] The temperature of the hydrothermal reaction is 140~160℃ and the time is 3~5 days;

[0033] The configuration method of aluminosilicate molecular sieve gel is:

[0034] Dissolve sodium hydroxide in water, then add the template, stir thoroughly until dissolved, add aluminum source and silicon source, stir thoroughly to obtain aluminosilicate molecular sieve gel;

[0035] The silicon source is one of silica sol, fumed silica or tetraethyl orthosilicate;

[0036] The aluminum source is one of sodium metaaluminate and aluminum isopropoxide;

[0037] The template agent is one or more of N, N, N-trimethyl-1-adamantyl ammonium hydroxide and tetrapropyl ammonium hydroxide;

[0038] The mass ratio of sodium hydroxide, water, template, aluminum source and silicon source is 1:15:(2.5~3.5):(0.05~0.06):1.

[0039] Aminated graphene was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XF243, which is aminated graphene oxide PEI modified with a size of 190-320 nm.

[0040] Preferably, the diameter of the boron nitride whisker is 0.5-1 μm and the length is 10-20 μm.

[0041] Boron nitride whiskers were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-BN-X2.

[0042] Preferably, the mass ratio of halloysite nanotubes, copper oxide and silicon titanium carbide is 1: (3-5): 1

[0043] The diameter of halloysite nanotubes is 100-200 nm and the length is 1-10 μm;

[0044] The average particle size of copper oxide is 80~100nm;

[0045] The average particle size of titanium silicon carbide is 5~10μm.

[0046] The mass ratio and specific parameters of halloysite nanotubes, copper oxide and silicon titanium carbide are defined in the present invention. By controlling the length and diameter of the halloysite nanotubes and the particle sizes of copper oxide and silicon titanium carbide, the pore structure of the composite material can be optimized, the influence of moisture on the pore structure can be reduced, the high specific surface area and good diffusion performance of the catalyst can be maintained, and the chance of sulfide diffusion into the interior of the catalyst can be reduced, thereby alleviating sulfur poisoning. By adjusting the mass ratio of halloysite nanotubes, copper oxide and silicon titanium carbide, the surface properties of the composite material can be optimized, so that it has better hydrophobicity or hydrophilicity, thereby improving the stability of the catalyst in a humid environment.

[0047] Halloysite nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model number XFI50.

[0048] Copper oxide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-CuO-02 or XT-CuO-03.

[0049] Titanium silicon carbide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., with the model number being XT-Ti3SiC2-01, XT-Ti3SiC2-02 or XT-Ti3SiC2-03.

[0050] Preferably, during the preparation of the modified inorganic material, the amount of ethanol added is 100-200% of the mass of the mixed material, the amount of sodium dodecyl sulfate added is 5-8% of the mass of the mixed material, the grinding speed is 300-500 rpm, and the time is 8-10 hours.

[0051] Preferably, in the preparation process of modified carboxymethyl cellulose, the mass ratio of carboxymethyl cellulose, water, ethylene oxide and diethyl phosphate is (1-3): (20-25): 1: 1, the reaction temperature after adding ethylene oxide is 45-55°C, the reaction time is 1-3h, and the reaction temperature after adding diethyl phosphate is increased to 60-80°C, the reaction time is 3-5h.

[0052] Preferably, in the preparation process of the organic-inorganic nanocomposite material, the mass ratio of the modified inorganic material to the modified carboxymethyl cellulose is 1: (5-10), the amount of ethanol added is 100-200% of the mass of the modified inorganic material, the amount of 3-aminopropyltriethoxysilane added is 5-10% of the mass of the modified inorganic material, the mass ratio of the modified carboxymethyl cellulose to water is 1: (15-20), the temperature of the heating reaction is 80-100°C, and the time is 2-4h.

[0053] Preferably, the organic binder is one or more of starch, gum arabic powder, dextrin, polyethylene glycol, and polyvinyl alcohol.

[0054] The second aspect of the present invention provides a method for preparing a Fe-SSZ-13 molecular sieve composite catalyst, comprising the following steps:

[0055] a) Add the synthesized Fe-SSZ-13 molecular sieve into 1 mol / L NH4Cl solution and mix evenly, wherein the solid-liquid ratio is 1:(100-150), stir at 60-80°C for 5-10 h, wash with deionized water, filter, and dry at 100-120°C for 10-12 h to obtain a modified Fe-SSZ-13 molecular sieve;

[0056] b) dry-mixing the modified Fe-SSZ-13 molecular sieve, the organic-inorganic nanocomposite material, and stearic acid to obtain a mixed material;

[0057] c) Add water to the mixture and stir at 80-85°C for 2-3 hours to control the moisture content of the material to 40-45%, then add boron nitride whiskers and glycerin and stir at 85-90°C for 0.5-1 hour to obtain a plastic clay material with a moisture content of 32-35%;

[0058] d) Extruding the plastic clay material through an extruder to obtain a honeycomb-shaped wet blank;

[0059] e) drying the honeycomb formed wet blank at 60-80° C. for 1-5 days to obtain a blank;

[0060] f) calcining the green body at 550-650°C for 3-6h to obtain a Fe-SSZ-13 molecular sieve composite catalyst.

[0061] A third aspect of the present invention provides an application of a Fe-SSZ-13 molecular sieve composite catalyst in removing nitrogen oxides in a selective catalytic reaction.

[0062] Therefore, the present invention adopts the above-mentioned Fe-SSZ-13 molecular sieve composite catalyst and its preparation method and application, which has the following beneficial effects:

[0063] 1. The Fe-SSZ-13 molecular sieve synthesized in the present invention is used as the main active component. It can effectively increase the dispersibility of Fe by introducing Fe-complex and synthesizing under hydrothermal conditions, thereby improving the catalytic activity of the catalyst. The addition of amination graphene can enhance the electron transfer ability of Fe-SSZ-13 molecular sieve and further improve the activity of the catalyst. The use of organic-inorganic nanocomposites increases the surface area and pore structure of the catalyst, which helps to improve the dispersibility of the active components and the diffusion efficiency of the reactants.

[0064] 2. The structural stability of the Fe-SSZ-13 molecular sieve synthesized in the present invention ensures the activity of the catalyst at higher temperatures, and the thermal stability of the catalyst can be further optimized by adjusting the hydrothermal reaction conditions. The addition of boron nitride whiskers helps to improve the thermal stability and mechanical strength of the catalyst, allowing the catalyst to maintain good performance in a wider temperature range.

[0065] 3. The synthesized Fe-SSZ-13 molecular sieve of the present invention has strong hydrothermal stability and sulfur resistance, and can effectively resist the influence of moisture and sulfide on the catalyst activity in actual working conditions. The organic components such as the carboxymethyl cellulose modified layer and 3-aminopropyltriethoxysilane in the organic-inorganic nanocomposite material provide additional protection, enhancing the water resistance and anti-sulfurization performance of the catalyst.

[0066] 4. The use of boron nitride whiskers in the present invention not only improves the mechanical strength of the catalyst, but also facilitates the rapid transfer of heat due to its good thermal conductivity, which is beneficial to improving the catalytic efficiency. The selection of organic binders (such as starch, gum arabic powder, etc.) helps to improve the formability and stability of the catalyst.

[0067] The technical solution of the present invention is further described in detail below through embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 This is the XRD pattern of the synthesized Fe-SSZ-13 molecular sieve. DETAILED DESCRIPTION

[0069] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0070] Example 1: This example provides a Fe-SSZ-13 molecular sieve composite catalyst, which includes the following raw materials in parts by weight:

[0071] Synthesize 70 parts of Fe-SSZ-13 molecular sieve;

[0072] Boron nitride whiskers 8 parts;

[0073] 16 parts of organic-inorganic nanocomposite materials;

[0074] 0.6 parts of stearic acid;

[0075] 1.5 parts of glycerol;

[0076] 4 parts of organic binder; the organic binder is starch.

[0077] The diameter of the boron nitride whisker is 0.5-1 μm, and the length is 10-20 μm; the boron nitride whisker was purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., model XT-BN-X2.

[0078] The preparation method of synthetic Fe-SSZ-13 molecular sieve comprises the following steps:

[0079] (1) The preparation method of Fe-complex solution is:

[0080] The iron source is added into water and stirred until it is completely dissolved to form an iron solution, a complexing agent is added dropwise into the iron solution, and the solution is stirred sufficiently to obtain an Fe-complex solution;

[0081] The iron source is ferric chloride; the complexing agent is disodium ethylenediaminetetraacetate;

[0082] The molar ratio of iron source to complexing agent is 0.4:0.5;

[0083] The mass volume ratio of iron source to water is 1 g:10 mL.

[0084] (2) The preparation method of aluminosilicate molecular sieve gel is:

[0085] Dissolve sodium hydroxide in water, then add the template, stir thoroughly until dissolved, add aluminum source and silicon source, stir thoroughly to obtain aluminosilicate molecular sieve gel;

[0086] The silicon source was tetraethyl orthosilicate;

[0087] The aluminum source is sodium metaaluminate;

[0088] The template agent is N, N, N-trimethyl-1-adamantyl ammonium hydroxide, CAS: 53075-09-5;

[0089] The mass ratio of sodium hydroxide, water, template, aluminum source and silicon source is 1:15:3:0.05:1.

[0090] (3) The Fe-complex solution was added dropwise to the aluminosilicate molecular sieve gel. After the addition was completed, amino graphene was added in an amount of 4% of the mass of the iron source. Ultrasonication was performed and the mixture was stirred evenly to carry out a hydrothermal reaction at a temperature of 150°C for 5 days. The mixture was filtered, washed and dried to obtain the synthesized Fe-SSZ-13 molecular sieve.

[0091] Aminated graphene was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XF243, which is aminated graphene oxide PEI modified with a size of 190-320 nm.

[0092] XRD test was performed on the synthesized Fe-SSZ-13 molecular sieve. Figure 1 It can be seen that the crystal structure of Fe-SSZ-13 molecular sieve is the same as that of H-SSZ-13 molecular sieve and Na-SSZ-13 molecular sieve, indicating that the addition of iron source and amino graphene will not affect the structure of the molecular sieve. Among them, Na-SSZ-13 molecular sieve refers to the original SSZ-13 molecular sieve that has not been treated with ion exchange, and the cations are mainly sodium ions (Na + ), the aluminosilicate molecular sieve gel in the present invention is directly subjected to hydrothermal reaction to obtain the H-SSZ-13 molecular sieve. The H-SSZ-13 molecular sieve refers to the SSZ-13 molecular sieve that has been treated with hydrogen exchange. The cations (usually sodium ions) originally present in the molecular sieve pores are replaced by hydrogen ions (H + ) is replaced, the Na-SSZ-13 molecular sieve is placed in 1M ammonium chloride ion exchange liquid and immersed at 60°C for 5h, washed and dried to obtain the product.

[0093] The preparation method of the organic-inorganic nanocomposite material comprises the following steps:

[0094] (1) mixing halloysite nanotubes, copper oxide and titanium silicon carbide to obtain a mixed material;

[0095] The mass ratio of halloysite nanotubes, copper oxide, and silicon titanium carbide is 1:4:1;

[0096] The diameter of the halloysite nanotubes is 100-200 nm, and the length is 1-10 μm; the halloysite nanotubes were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XFI50.

[0097] The average particle size of copper oxide is 80 nm; copper oxide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-CuO-02.

[0098] The average particle size of titanium silicon carbide is 8 μm; titanium silicon carbide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., with the model number being XT-Ti3SiC2-02.

[0099] (2) adding the mixed material into a ball mill, and then adding ethanol and sodium dodecyl sulfate into the ball mill, wherein the amount of ethanol added is 120% of the mass of the mixed material, and the amount of sodium dodecyl sulfate added is 6% of the mass of the mixed material, and then adding grinding media for grinding, the grinding speed is 450 rpm, and the time is 9 hours. After the grinding is completed, filtering, washing, and drying to obtain a modified inorganic material;

[0100] (3) dissolving carboxymethyl cellulose in water to form a carboxymethyl cellulose solution, adding ethylene oxide to the carboxymethyl cellulose solution, and heating the reaction at 40°C for 2 hours. Then, diethyl phosphate is added, and after the reaction is completed, the reaction temperature is raised to 65°C for 4 hours. The reaction is filtered, washed, and dried to obtain modified carboxymethyl cellulose.

[0101] The mass ratio of carboxymethyl cellulose, water, ethylene oxide, and diethyl phosphate is 2:22:1:1;

[0102] (4) adding the modified inorganic material into ethanol and 3-aminopropyltriethoxysilane, wherein the amount of ethanol added is 110% of the mass of the modified inorganic material, and the amount of 3-aminopropyltriethoxysilane added is 6% of the mass of the modified inorganic material, and reacting at room temperature to obtain a mixed solution 1;

[0103] Adding modified carboxymethyl cellulose into water to form mixed solution 2, the mass ratio of modified carboxymethyl cellulose to water is 1:16;

[0104] The mixed solution 1 is added to the mixed solution 2, the mass ratio of the modified inorganic material to the modified carboxymethyl cellulose is 1:6, the heating reaction temperature is 90°C, the time is 2h, and the organic-inorganic nanocomposite material is obtained by filtering, washing and drying.

[0105] A method for preparing a Fe-SSZ-13 molecular sieve composite catalyst comprises the following steps:

[0106] a) The synthesized Fe-SSZ-13 molecular sieve was added to a 1 mol / L NH4Cl solution and mixed evenly, wherein the solid-liquid ratio was 1:100, stirred at 70°C for 8 h, washed with deionized water, filtered, and dried at 110°C for 10 h to obtain a modified Fe-SSZ-13 molecular sieve;

[0107] b) dry-mixing the modified Fe-SSZ-13 molecular sieve, the organic-inorganic nanocomposite material, and stearic acid to obtain a mixed material;

[0108] c) Add water to the mixture and stir at 80°C for 2 hours to control the moisture content of the material to 42%, then add boron nitride whiskers and glycerin and stir at 90°C for 0.8 hours to obtain a plastic clay material with a moisture content of 33%;

[0109] d) Extruding the plastic clay material through an extruder to obtain a honeycomb-shaped wet blank;

[0110] e) drying the honeycomb formed wet blank at 70° C. for 3 days to obtain a blank;

[0111] f) The green body was calcined at 600°C for 5 hours to obtain a Fe-SSZ-13 molecular sieve composite catalyst.

[0112] Example 2: The difference between this example and Example 1 is that the formula of the Fe-SSZ-13 molecular sieve composite catalyst is different.

[0113] In this embodiment, the Fe-SSZ-13 molecular sieve composite catalyst includes the following raw materials in parts by weight:

[0114] Synthesize 60 parts of Fe-SSZ-13 molecular sieve;

[0115] Boron nitride whiskers 8 parts;

[0116] 18 parts of organic-inorganic nanocomposite materials;

[0117] 0.5 parts of stearic acid;

[0118] 2 parts glycerin;

[0119] 5 parts of organic binder;

[0120] The organic binder is gum arabic powder.

[0121] The diameter of the halloysite nanotube is 150 nm and the length is 5 μm; the halloysite nanotube is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model number is XFI50.

[0122] The average particle size of copper oxide is 100 nm; copper oxide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-CuO-03.

[0123] The average particle size of titanium silicon carbide is 5 μm; titanium silicon carbide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., and the model number is XT-Ti3SiC2-01.

[0124] Comparative Example 1

[0125] The difference between this comparative example and Example 1 is that no amination graphene is added during the preparation of the synthetic Fe-SSZ-13 molecular sieve.

[0126] Comparative Example 2

[0127] The difference between this comparative example and Example 1 is that the mixed material is not subjected to a ball milling process, and the mixed material is directly placed in the second mixed solution.

[0128] Comparative Example 3

[0129] The difference between this comparative example and Example 1 is that 3-aminopropyltriethoxysilane is not added to the mixed solution 1.

[0130] Comparative Example 4

[0131] The difference between this comparative example and Example 1 is that no ethylene oxide is added during the preparation of the modified carboxymethyl cellulose.

[0132] Comparative Example 5

[0133] The difference between this comparative example and Example 1 is that diethyl phosphate is not added during the preparation of the modified carboxymethyl cellulose.

[0134] Comparative Example 6

[0135] The difference between this comparative example and Example 1 is that the mass ratio of halloysite nanotubes, copper oxide and silicon titanium carbide is 1:10:1.

[0136] Comparative Example 7

[0137] The difference between this comparative example and Example 1 is that the parameters of the halloysite nanotubes are different. The diameter of the halloysite nanotubes is 300 nm and the length is 5 μm. The halloysite nanotubes are purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., and the model is XFI50.

[0138] Comparative Example 8

[0139] The difference between this comparative example and Example 1 is that the average particle size of copper oxide is different. The average particle size of copper oxide is 300 nm. The copper oxide is purchased from Shanghai Xiangtian Nanomaterial Co., Ltd. and the model is XT-CuO-04.

[0140] Comparative Example 9

[0141] The difference between this comparative example and Example 1 is that the average particle size of titanium silicon carbide is different, and the average particle size of titanium silicon carbide is 20 μm; titanium silicon carbide is purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., and the model is XT-Ti3SiC2-04.

[0142] Comparative Example 10

[0143] The difference between this comparative example and Example 1 is: the type of amination graphene, this comparative example uses hydroxylation graphene powder purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model XF307, sheet diameter 1-3 μm, thickness 1-5 nm.

[0144] Performance Testing

[0145] The test conditions of the composite catalyst obtained in the embodiment and the comparative example are 500ppm of nitric oxide, 500ppm of ammonia, 1000ppm of sulfur dioxide, 10% of water vapor, 10% of oxygen, the reaction balance gas is nitrogen, the loading amount of the composite catalyst is 90ml, and the reaction space velocity is 10000h -1 The catalytic effect of the composite catalyst is shown in Table 1.

[0146] NO x Conversion rate =

[0147] Among them (NO x ) in is the initial nitrogen oxide concentration, (NO x ) out is the concentration of nitrogen oxides after catalytic reaction.

[0148] Table 1 Catalytic performance test results

[0149]

[0150] It can be seen from the above performance test results that the composite catalyst prepared in Examples 1-2 has the best catalytic effect and also has excellent water resistance and sulfur resistance. In particular, the comprehensive performance of Example 1 is the most outstanding. This is mainly because the present invention not only adjusts the preparation method of Fe-SSZ-13 molecular sieve, but also specifically adds organic-inorganic nanocomposite materials, which significantly improves the catalytic activity and water and sulfur resistance, and extends the service life of the catalyst.

[0151] The comparative example is not adopted the necessary technical scheme, which leads to the fact that it is obviously worse than the embodiment in the corresponding performance test. In the comparative example 1, the catalytic activity of the catalyst decreases during the preparation of the Fe-SSZ-13 molecular sieve. It can be seen from the results that the catalytic activity of the catalyst decreases, proving that the addition of the catalytic effect of the catalytic effect is significantly affected. The inorganic mixed material in the comparative example 2 is not ball-milled, and it can be seen from the results that the catalytic activity of the catalyst at different temperatures is affected, and as the temperature increases, the catalytic activity also decreases, because the higher the temperature, the greater the structural influence of moisture and sulfur dioxide on the catalyst, resulting in a lower conversion rate of nitrogen oxides, indicating that the bonding force between various raw materials can be increased after the mixed material is ball-milled, thereby affecting the comprehensive performance of the catalyst. 3-aminopropyl triethoxy silane is not added in the comparative example 3, which directly affects the interfacial bonding force between the inorganic material and the organic material, thereby affecting the pores and structure of the catalyst, and it can be seen from the results that the comprehensive performance of the composite catalyst prepared by it decreases, indicating that 3-aminopropyl triethoxy silane has an important influence on the performance of the catalyst. In Comparative Examples 4 and 5, ethylene oxide and diethyl phosphate were not added when the carboxymethyl cellulose was modified. It can be seen from the results that not only the catalytic activity of the catalyst decreased, but also the water resistance and sulfur resistance of the catalyst decreased to varying degrees, indicating that the modification of the carboxymethyl cellulose in the present invention has a very important influence on the comprehensive performance of the catalyst. Comparative Examples 6 to 9 respectively changed the mass ratio and particle size of halloysite nanotubes, copper oxide and silicon titanium carbide. It can be seen from the results that the catalytic performance of the composite catalyst prepared therefrom has decreased significantly, and with the increase in temperature, the influence of sulfur dioxide and moisture in the flue gas on the catalyst structure is aggravated, resulting in a significant decrease in catalytic activity, which indicates that the addition ratio and particle size of inorganic materials will directly affect the structure of the catalyst, which plays an important role in improving the comprehensive performance of the catalyst. Comparative Example 10 changes the type of amination graphene. It can be seen from the results that compared with the embodiment, its catalytic activity has decreased significantly, indicating that the type of amination graphene has an important influence on the comprehensive performance of the catalyst. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0152] Therefore, the present invention adopts an Fe-SSZ-13 molecular sieve composite catalyst with the above structure and its preparation method and application. The prepared Fe-SSZ-13 molecular sieve composite catalyst not only has high catalytic activity and a wide operating temperature range, but also has good hydrothermal stability and sulfur resistance. The addition of boron nitride whiskers significantly improves the mechanical properties and wear resistance of the catalyst, and is suitable for long-term operation under industrial conditions.

[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A Fe-SSZ-13 molecular sieve composite catalyst, characterized in that: The following raw materials are included in parts by weight: Synthetic Fe-SSZ-13 molecular sieve 60~80 parts Boron nitride whiskers 5~10 parts 15~20 parts of organic-inorganic nanocomposite materials 0.5~1 part of stearic acid 1~2 parts glycerin 3~5 parts of organic binder; The preparation method of synthetic Fe-SSZ-13 molecular sieve is: The Fe-complex solution is added dropwise to the aluminosilicate molecular sieve gel, and after the addition is completed, amino graphene is added, ultrasonicated and stirred evenly, a hydrothermal reaction is carried out, and the mixture is filtered, washed and dried to obtain a synthetic Fe-SSZ-13 molecular sieve; The preparation method of the organic-inorganic nanocomposite material is as follows: (1) mixing halloysite nanotubes, copper oxide and titanium silicon carbide to obtain a mixed material; (2) adding the mixed material into a ball mill, then adding ethanol and sodium dodecyl sulfate into the ball mill, and then adding a grinding medium for grinding. After the grinding is completed, filtering, washing, and drying to obtain a modified inorganic material; (3) dissolving carboxymethyl cellulose in water to form a carboxymethyl cellulose solution, adding ethylene oxide to the carboxymethyl cellulose solution, and after the heating reaction is completed, continuing to add diethyl phosphate, and after the temperature is raised to complete the reaction, filtering, washing, and drying to obtain modified carboxymethyl cellulose; (4) adding the modified inorganic material to ethanol and 3-aminopropyltriethoxysilane, reacting at room temperature to obtain a mixed solution 1, adding the modified carboxymethyl cellulose to water to form a mixed solution 2, adding the mixed solution 1 to the mixed solution 2, heating to react, filtering, washing, and drying to obtain an organic-inorganic nanocomposite material; The mass ratio of halloysite nanotubes, copper oxide and silicon titanium carbide is 1:(3~5):1; The diameter of halloysite nanotubes is 100-200 nm and the length is 1-10 μm; The average particle size of copper oxide is 80~100nm; The average particle size of titanium silicon carbide is 5~10μm.

2. The Fe-SSZ-13 molecular sieve composite catalyst according to claim 1, characterized in that: The preparation method of Fe-complex solution is: The iron source is added into water and stirred until it is completely dissolved to form an iron solution, a complexing agent is added dropwise into the iron solution, and the solution is stirred sufficiently to obtain an Fe-complex solution; The iron source is one of ferric chloride and ferric nitrate; the complexing agent is one of N-aminoethyl-γ-aminopropyltrimethylsilane and disodium ethylenediaminetetraacetate; The molar ratio of iron source to complexing agent is 0.3~0.5:0.1~1; The amount of amino graphene added is 3-5% of the mass of the iron source; The temperature of the hydrothermal reaction is 140~160℃ and the time is 3~5 days; The configuration method of aluminosilicate molecular sieve gel is: Dissolve sodium hydroxide in water, then add the template, stir thoroughly until dissolved, add aluminum source and silicon source, stir thoroughly to obtain aluminosilicate molecular sieve gel; The silicon source is one of silica sol, fumed silica or tetraethyl orthosilicate; The aluminum source is one of sodium metaaluminate and aluminum isopropoxide; The template agent is one of N,N,N-trimethyl-1-adamantyl ammonium hydroxide and tetrapropyl ammonium hydroxide; The mass ratio of sodium hydroxide, water, template, aluminum source and silicon source is 1:15:(2.5~3.5):(0.05~0.06):

1.

3. The Fe-SSZ-13 molecular sieve composite catalyst according to claim 1, characterized in that: The diameter of boron nitride whiskers is 0.5~1μm and the length is 10~20μm.

4. The Fe-SSZ-13 molecular sieve composite catalyst according to claim 1, characterized in that: During the preparation of the modified inorganic material, the amount of ethanol added is 100-200% of the mass of the mixed material, the amount of sodium dodecyl sulfate added is 5-8% of the mass of the mixed material, the grinding speed is 300-500 rpm, and the time is 8-10 hours.

5. The Fe-SSZ-13 molecular sieve composite catalyst according to claim 1, characterized in that: During the preparation of modified carboxymethyl cellulose, the mass ratio of carboxymethyl cellulose, water, ethylene oxide and diethyl phosphate is (1~3):(20~25):1:

1. The heating reaction temperature after adding ethylene oxide is 45~55°C and the time is 1~3h. After adding diethyl phosphate, the reaction temperature rises to 60~80°C and the time is 3~5h.

6. The Fe-SSZ-13 molecular sieve composite catalyst according to claim 1, characterized in that: In step (4), the mass ratio of the modified inorganic material to the modified carboxymethyl cellulose is 1:(5-10), the amount of ethanol added is 100-200% of the mass of the modified inorganic material, the amount of 3-aminopropyltriethoxysilane added is 5-10% of the mass of the modified inorganic material, the mass ratio of the modified carboxymethyl cellulose to water is 1:(15-20), the temperature of the heating reaction is 80-100°C, and the time is 2-4h.

7. The Fe-SSZ-13 molecular sieve composite catalyst according to claim 1, characterized in that: The organic binder is one or more of starch, gum arabic powder, dextrin, polyethylene glycol and polyvinyl alcohol.

8. The method for preparing a Fe-SSZ-13 molecular sieve composite catalyst according to any one of claims 1 to 7, characterized in that: The following steps are involved: a) Add the synthesized Fe-SSZ-13 molecular sieve into 1 mol / L NH4Cl solution and mix evenly, wherein the solid-liquid ratio is 1:(100-150), stir at 60-80°C for 5-10 h, wash with deionized water, filter, and dry at 100-120°C for 10-12 h to obtain a modified Fe-SSZ-13 molecular sieve; b) dry-mixing the modified Fe-SSZ-13 molecular sieve, the organic-inorganic nanocomposite material, and stearic acid to obtain a mixed material; c) Add water to the mixture and stir at 80-85°C for 2-3 hours to control the moisture content of the material to 40-45%, then add boron nitride whiskers and glycerin and stir at 85-90°C for 0.5-1 hour to obtain a plastic clay material with a moisture content of 32-35%; d) Extruding the plastic clay material through an extruder to obtain a honeycomb-shaped wet blank; e) drying the honeycomb formed wet blank at 60-80° C. for 1-5 days to obtain a blank; f) calcining the green body at 550-650°C for 3-6h to obtain a Fe-SSZ-13 molecular sieve composite catalyst.

9. Use of a Fe-SSZ-13 molecular sieve composite catalyst as claimed in any one of claims 1 to 7 in removing nitrogen oxides in a selective catalytic reaction.

Citation Information

Patent Citations

  • High heat-conduction ceramic heat-radiation nanocomposite material used for LED lamp

    CN107434414A

  • Composite molecular sieve denitration catalyst, and preparation method and application thereof

    CN107552088A